Symptoms and self-care following pancreaticoduodenectomy: Perspectives from patients and healthcare professionals - Foundation for an interactive ICT application. (February 2017) - Gustavell, Tina; Sundberg, Kay; Frank, Catharina; Wengström, Yvonne; Browall, Maria; Segersvärd, Ralf; Langius-Eklöf, Ann
Abstract: Purpose: Poor prognosis and a problematic recovery period after pancreaticoduodenectomy means that patients may benefit from early detection of symptoms and support for self-management. Interactive Information and Communication Technology tools can be used for this purpose, but the content needs to be relevant to patients as well as healthcare professionals. To facilitate development of the content of an application for this purpose, the aim of this study was to explore common symptoms and self-care in the first six months after pancreaticoduodenectomy, as identified by patients and healthcare professionals. Method: Data were collected through individual interviews with patients (n = 14), along with two focus group interviews and one individual interview with healthcare professionals (n = 10). Data were analysed using qualitative content analysis. Results: Common symptoms after surgery were those related to eating, bowel function and emotional wellbeing, along with fatigue and pain. Some self-care activities and advice were mentioned in the interviews. The patients often experienced a lack of advice on self-care at discharge. Conclusions: The results render knowledge of the symptoms it is important to be aware of and to assess regularly after pancreaticoduodenectomy. The results also contribute to knowledge about specific self-care related to these symptoms, even though it was not extensively described, and further research is needed to define evidence-based self-care advice. Highlights: Patients experience symptoms several months following pancreaticoduodenectomy. Evidence-based self-care advice following pancreaticoduodenectomy is deficient. There was a discrepancy between received and given self-care advice. Symptoms should regularly be assessed after discharge to identify problems early.